PENENTUAN WAKTU EFEKTIF SELAMA FASE LUTEAL DALAM SINKRONISASI ESTRUS MENGGUNAAN PGF2Î‘ PADA KAMBING KACANG - Jusak Labetubun; I. P. Siwa; Ferdenanda Reressy (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
This study aims to determine the effective time during the luteal phase in the synchronization of lust using, PGF2Î± on kacang goat. A total of nine simple 1.5-year-old goat-bean goats were randomly grouped into three treatments at the time of injection in the respective luteal phase; injection of the 6th day after the first injection as P1, injection of the 8th day as P2 and Injection of the 10th day as P3. The research variables are the time of the onset of estrus (onset estrus), signs of estrus and pregnancy rate. The results of the study were tabulated and analyzed statistically using a completely randomized directional design in the MINITAB Version 14. The results of the study concluded that the treatment factor was significantly different (P <0.01) with respect to the onset of estrus. Where the injection during the luteal phase, both on the 6th day, the 8th day and on the 10th day, both provide a good and very real response to the onset of estrus. But the P3 treatment that is the 10th day injection is better with an average onset of estrus 5.31 hours, then the treatment P2 with the onset of estrus 26.78 hours and the treatment of P1 with the onset of estrus 38.87 hours. Signs of lust are the same for all cattle with a pregnancy rate of 100%.